Apakah Beban Operasional Pendapatan Operasional, Capital Adequacy Ratio dan Non-Performing Loan Berhubungan Dengan Pertumbuhan Laba? - Cut Delsie Hasrina; Sindi Ayuni; Marah Sutan Rangkuti (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to determine the magnitude of the partial and simultaneous influence of operating expenses, operating income, capital adequacy ratio and non-performing loans on profit growth in banking sector companies listed on the Indonesia. The technique used as an analytical tool in this study is by using multiple linear regression analysis with the help of the SPSS version 23 program. The results of the study indicate that operating expenses, operating income, have an effect on profit growth in banking sector companies listed on the Indonesia Stock Exchange with a β1 value of 0.302 with the calculation result β1 ≠ 0 or the calculated t value (3.974) is greater than the t-table value (2.000). Capital adequacy ratio has an effect on profit growth in banking sector companies listed on the Indonesia Stock Exchange with a β2 value of 0.206 with the calculation result of β2 ≠ 0 or the calculated t value (2.512) is greater than the t table value (2.000). Non-performing loans have an effect on profit growth in banking sector companies listed on the Indonesia Stock Exchange with a β3 value of 0.211 with the calculation result of β3 ≠ 0 or the calculated t value (2.637) is greater than the t table value (2.000). Operating expenses, operating income, capital adequacy ratio and non-performing loans simultaneously have an effect on profit growth in banking sector companies listed on the Indonesia Stock Exchange with an F calculated value (15.986) greater than the F table value (2.758).